THE FACTORS AFFECTING THE QUALITY OF YARN PRODUCED ON RING-SPINNING MACHINES - Alihanov Sharifhon Saidolimhon ogli; Bobojanov Husanhon Toxirovich; Yusupov Alijon Abdujabbor ogli; Yusupov Sabrjon Abdujabborovich (European Journal of Interdisciplinary Research and Development, 2023)
The article compares the unevenness of the linear density of 20 tex yarn, produced on a ring spinning machine at twist speeds of 11000, 12000, 13000, 14000, and 15000 twists of 740 rpm.